Exploring Distractions Impacting Arab EFL Learners in Online Environments - Barkaoui, Mohamed Elboussairi Salih Elhaj Mohamed (Journal of Educational Science and Technology (EST), 2024)
This study investigates key distractions impacting Arab EFL learners in online education, shaped by unique socio-cultural, technological, and environmental factors. Using a qualitative approach, semi-structured interviews with ten online teaching experts from the Arab region identified primary distraction sources and context-specific solutions. Thematic analysis revealed four main types of distractions: cultural influences, technological limitations, household interruptions, and low engagement levels, all significantly hindering students’ focus and academic performance. Experts recommended strategies to address these challenges, including enhancing digital infrastructure, integrating culturally aware teaching practices, creating supportive learning spaces, and leveraging interactive tools to improve engagement. The findings emphasize the need for solutions tailored to the Arab context, offering practical guidance for educators, policymakers, and institutions to create more effective online learning environments. This research provides valuable insights into the distinct challenges faced by Arab EFL learners, promoting a more customized approach to support their success in online education.